Gene doping: the hype and the harm - McKanna, T. A.; Toriello, H. V. (Pediatric Clinics of North America, 2010)
"Gene doping" is the term used to describe the potential abuse of gene therapy as a performance-enhancing agent. Gene doping would apply the techniques used in gene therapy to provide altered expression of genes that would promote physical superiority. For example, insulin-like growth factor 1 (IGF-1) is a primary target for growth hormone; overexpression of IGF-1 can lead to increased muscle mass and power. Although gene doping is still largely theoretical, its implications for sports, health, ethics, and medical genetics are significant.